Utilizing the Theology of Religions and Human Geography to Understand the Spatial Dimension of Religion and Conflict - Harris, Elizabeth J. (Religions, 2022)
This paper argues for an interdisciplinary approach within the study of religion and conflict. Using a religious studies framework, it demonstrates that tools from human geography, peace studies, and the theology of religions can be used to shed light on the intractability of conflicts where religion is not "innocent". Within human geography, the spatial dimension of individual and communal identity, most particularly the concept of "mythical space", can illuminate the non-empirical, affective factors that condition attitudes to religious and ethnic others. Similarly, within the theology of religions, the typology of exclusivism, inclusivism, and pluralism can aid understanding of tendencies within all human communities, religious and non-religious, when faced with perceived threats from significant others. Two case studies, Sri Lanka and Israel/Palestine, are examined through this interdisciplinary approach, using illustrative "moments" within each conflict. Both highlight the affective power of primal imaginaries that are informed by narratives about religion, land, and identity. Without dismissing the importance of political and economic factors in the arising of conflict, this paper argues that it is not enough to analyse these factors alone. Other disciplines are necessary and this paper argues for two important examples: human geography and the theology of religions.